WOMEN’S LANGUAGE FEATURES USED IN AN INTERVIEW VIDEO “WHO DOES TIFFANY YOUNG LOOK UP TO?” - Ni Kadek Nanik Dwiantari (British (Jurnal Bahasa dan Sastra Inggris), 2023)
This study entitled Women’s Language Features Used in an Interview Video “Who does Tiffany Young Look Up To?”. The aims are to identify the features of women’s language and to identify the language functions served by women’s language features found in an exclusive interview video. The analysis of women’s language features was based on the theory which was proposed by Lakoff and theory by Jakobson was applied in analyzing the language functions. This research was conducted by using qualitative method. In collecting the data, it was used documentation method. For the findings, there are seven features of women’s language found in the video, they are lexical hedges or fillers, rising intonation on declaratives, empty adjective, intensifiers, hypercorrect grammar, super polite forms and emphatic stress feature. For the functions of language, it was found that the utterances used emotive or expressive and conative or directive function.